ANTIMICROBIAL ACTIVITY OF A SYNTHETIC BACTERIOCIN FOUND IN THE GENOME OF LACTOBACILLUS CASEI ON THE MICROBIOTA OF ANTIOQUIAN SOFT CHEESE (QUESITO ANTIOQUEÑO) - Bolivar Parra, Laura; Giraldo Hincapié, Paula Andrea; Montoya Campuzano, Olga Inés (Vitae, 2020)
Background: Lactic Acid Bacteria (LAB) are of special interest in the food industry due to their ability to produce metabolites. Among them, bacteriocins, which can inhibit the growth of altering microorganisms, and pathogens in a wide variety of foods, are considered safe for human consumption and are used as preservatives. Objectives: Evaluate the effect of a bacteriocin found by in silico methods on the microbiota present in Antioquian soft cheese. Methods: In this research, we design a synthetic bacteriocin, called Bac 22, found in the genome of Lactobacillus casei using the genomic mining methodology and bioinformatics tools. We also conducted a preliminary biological and hemolytic activities studies of the Bac 22 toward the microbiota present in the Antioquian soft cheese (Quesito Antioqueño). Results: The bacteriocin Bac 22 at a concentration of 100 μM presented a hemolytic capacity lower than 1% and reduced the CFU / g of total coliforms significantly when added to Antioquian soft cheese for eight days. Conclusions: The Bac 22 demonstrated a positive potential effect over the shelf life of a dairy product, such as the Antioquian soft cheese.